Clinical and Histopathological Characteristics of Psoriasis in Dr. Hasan Sadikin General Hospital Bandung from 2009 to 2013 - Hermawan, Willy Chandra; Aminah, Hermin; Sandiono, Dendi (Althea Medical Journal, 2016)
Background: Psoriasis is a chronic inflammatory skin disease characterized by alterations in epidermal growth and differentiation. Its primary cause remains unknown, and its clinical and histopathological characteristics sometimes change from time to time. The study aimed to reveal the clinical and histopathological characteristics among psoriasis patients in Dr. Hasan Sadikin General Hospital Bandung.Methods: This study involved 162 medical records of psoriasis patients who visited the Department of Dermato-Venereology and 40 medical records of psoriasis patients who visited the Department of Pathological Anatomy of Dr. Hasan Sadikin Hospital, from 2009 to 2013. Medical record data were collected to describe the patientâs clinical and histopathological characteristics of psoriasis. The collected data were analyzed by frequency distribution.Results: From the clinical medical records, the characteristics found among the psoriasis patients were: 14 (8.6%) having familial history, 160 (98.8%) having reddish plaque, 155 (95.7%) having silvery scale, 40 (24.7%) having pustules, 6 (3.7%) having positive Auspitz sign, 48 (29.6%) having nail involvement, and 20 (12.4%) having tongue involvement. In addition, from the histopathological medical records, the characteristics of epidermis among the psoriasis patients found were: 36 (90%) having hyperkeratosis with parakeratosis, 39 (98%) having rete ridge elongation and/or acanthosis, 35 (88%) having Munroâs microabcess and/or micropustules of Kogoj, 15 (38%) having thin stratum granulosum, and 30 (75%) having blood vessels dilatation.Conclusions: In psoriasis, the most common clinical characteristics are reddish plaque while the most common histopathological characteristics are elongation of the rete ridges and/or acanthosis. [AMJ.2016;3(4):556â61]Â DOI:Â 10.15850/amj.v3n4.938